CCL2, CCL3 and CCL4 gene polymorphisms in pulmonary tuberculosis patients of South India. (3rd September 2013) - Singh, B.; Chitra, J.; Selvaraj, P.
Summary Polymorphisms in chemokine genes are important to determine the host–pathogen interactions which influence the chemokine levels. This study was carried out to find whether various CC chemokine gene polymorphisms, located in the promoter, exon‐2 and intron‐1 regions are associated with susceptibility or resistance to pulmonary tuberculosis (PTB) in south Indian population. The polymorphisms in various CC chemokine genes, MCP‐1 (CCL2) [−2518A/G, 903C/T], MIP‐1α (CCL3) [−2021C/T, +740A/G] and MIP‐1β (CCL4) [−5725A/C] were studied in 295 healthy controls (HCs) and 303 patients with PTB using polymerase chain reaction‐based restriction fragment length polymorphism (PCR‐RFLP). The allele and genotype frequencies of CCL2, CCL3 and CCL4 were not different between HCs and patients with PTB. However, a significantly decreased frequency of CCL2 −2518GG genotype was observed in male patients with PTB [P value = 0.015, P corrected (Bonferroni correction) Pc = 0.045, odds ratio (OR) 0.43 95% CI (0.21–0.86)], and a significantly increased frequency of the same genotype was observed among female patients with PTB [P value = 0.049, Pc = 0.147, OR 2.28 95% CI (1.00–5.27)]. The results suggest that −2518GG genotype may be associated with protection in males and susceptibility to PTB in females. Moreover, we also observed differences in the haplotype frequencies of these chemokine genes between HCs and patients with PTB. However, these polymorphisms are not associated with disease independently, probably in combination with other genes, they may be associated with susceptibility or resistance to TB in south Indian population.